A randomised clinical study to evaluate experimental children's toothpastes in an in‐situ palatal caries model in children aged 11–14 years. (December 2013) - Newby, Evelyn E.; Martinez‐Mier, Esperanza A.; Hara, Anderson; Lippert, Frank; Kelly, Sue A.; Fleming, Nancy; Butler, Andrew; Bosma, Mary Lynn; Zero, Domenick T.
Abstract : Objectives: To compare three children's sodium fluoride toothpastes to placebo with respect to enamel remineralisation potential, enamel fluoride uptake and net acid resistance using an in situ palatal caries model in children aged 11–14 years following a single brushing. Design: This was a randomised, single blind (laboratory analyst), single‐centre, four‐treatment, crossover study with a 7‐day washout period between treatments. The treatments were 1, 426 ppm fluoride, 1, 000 ppm fluoride, 500 ppm fluoride and 0 ppm fluoride (placebo) toothpaste (NaF/silica). A custom made in situ palatal appliance was used by each subject in all treatment periods. At each of the four treatment visits subjects wore the appliance containing four partially demineralised human enamel specimens for 5 minutes and then brushed their teeth using a standardised procedure for 60 seconds under supervision using 1.0 g (±0.1 g) of their assigned toothpaste. After 4 hours the appliance was removed and enamel specimen recovered. This process was repeated until all subjects completed all four study treatment visits. Recovered enamel specimens were analysed for per cent surface microhardness recovery (%SMHR; Knoop) and enamel fluoride uptake (EFU; microdrill biopsy). Subsequently, specimens were demineralised in vitro to determine their % net acid resistance (%NAR; Knoop). Results: All three fluoride toothpastes demonstrated significantly greater %SMHR, EFU and %NAR compared with 0 ppm F toothpaste. The model demonstrated a dose response over the range 0 to 1, 426 ppm fluoride for %SMHR, EFU and %NAR. There was no significant difference between 500 ppm F and 1, 000 ppm F for %SMHR and between 1, 000 ppm F and 1, 426 ppm F for %SMHR, EFU and %NAR. Conclusions: The present in situ study demonstrated that the children's fluoride toothpastes tested are capable of delivering cariostatic amounts of fluoride to early caries lesions following a single brushing.